2015
DOI: 10.1016/j.ijhm.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A spatial–temporal analysis of hotels in urban tourism destination

Abstract: a b s t r a c tThis study investigates the spatial associations of urban tourism phenomena by using GIS and statistical methods to examine the relationships between hotels and land use types, attractions, transportation facilities, and the economic variables of the tertiary planning units in which the hotels are located. Hong Kong is used as an example. The study first introduces the spatial characteristics of hotels and attractions development in Hong Kong. A geographical information system is then used to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 39 publications
1
56
1
4
Order By: Relevance
“…More recently, Kang et al (2014) have demonstrated the application of GIS-based ESDA in the assessment of the changing distribution of domestic tourism in South Korea between 1989 and 2011. Li et al (2014) employed GIS tools and statistical models to investigate the spatial associations of urban tourism phenomena by examining the spatial relationships between hotel distribution and land types, attractions and other surrounding environmental factors in Hong Kong. In another register, Zhang et al (2011) investigated the spatial dependence and the mechanisms of international and domestic tourist distributions in Chinese cities by means of ESDA based on GIS techniques.…”
Section: Spatial Autocorrelation Analysismentioning
confidence: 99%
“…More recently, Kang et al (2014) have demonstrated the application of GIS-based ESDA in the assessment of the changing distribution of domestic tourism in South Korea between 1989 and 2011. Li et al (2014) employed GIS tools and statistical models to investigate the spatial associations of urban tourism phenomena by examining the spatial relationships between hotel distribution and land types, attractions and other surrounding environmental factors in Hong Kong. In another register, Zhang et al (2011) investigated the spatial dependence and the mechanisms of international and domestic tourist distributions in Chinese cities by means of ESDA based on GIS techniques.…”
Section: Spatial Autocorrelation Analysismentioning
confidence: 99%
“…The specific set of linkages among a defined set of entities in the network may be used to interpret the behaviour of the entities involved (Mitchell, 1969). Moreover, the analysis is theoretically important as it enriches the methodologies not only for analysing the relationships but also for conceptualizing and identifying tourism functional zones (Li et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The statistical methods for categorical data are useful for this study since the majority of building attributes are categorical data. Logistic regression was used to validate the spatial pattern of changes [34,35], and a chi-square test of independence to find out the relation between touristic usage and significant changes in the built environment [36]. The entire cohort of buildings in the six villages was analyzed.…”
Section: Significant Changes In Built Environmentmentioning
confidence: 99%
“…A logistic regression was employed to validate the spatial pattern of increase of touristic usage in the built environment [34,35]. R software was used for the analysis [37].…”
Section: Spatial Pattern Of Increase Of Touristic Usagementioning
confidence: 99%
See 1 more Smart Citation